Arthroscopic Treatment of Chronic Cruciate Ligament Rupture in the Dog without Stifle Stabilization: 13 Cases (2001-2020). (11th April 2023) - Creamer, Danielle G.; Muir, Peter
Abstract : Objective . The objective was to study clinical outcomes in dogs with chronic cruciate ligament rupture (CR) treated with palliative arthroscopy as the sole surgical treatment. Methods . Thirteen client-owned dogs with CR underwent physical examination, stifle radiography, and arthroscopy with resection of damaged meniscal tissue. Records were evaluated, and orthopaedic examination, radiographs, and arthroscopy images were assessed. Long-term clinical outcome was also assessed by use of an owner questionnaire. Results . Thirteen dogs that underwent arthroscopy at the UW Veterinary Care between 2001 and 2020 were included. Long-term follow-up was available for 7 of 13 dogs. Lameness was static to improved in all dogs in which arthroscopy was performed. Subsequent stifle stabilization was performed after arthroscopy in only 1 of 7 dogs with follow-up data. Conclusion . Palliative arthroscopy and resection of damaged meniscal tissue in combination with medical management of osteoarthritis can be considered in dogs with chronic CR and cranial tibial subluxation with little passive laxity during examination. Revision surgery with TPLO is uncommon after arthroscopy based on this study.